Desa Tangguh Bencana Sebagai Upaya Pemulihan Mental Dan Kondisi Sosial Pasca Bencana Di Desa Bades - indira Tunjung Putih; Ignatia Martha Hendrati; Anisa Fitria Utami (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Trauma is a condition caused by old wounds that occurred in the past and requires psychological treatment to restore an effective life. There is also the impact of trauma condition on the economy of the residents of Bades Village, Pasirian District, Lumajang Regency. Trauma Healing is the process for someone who want to forget the chaotic feelings of something that has happened and decided to continue living in peace without anxious. The purpose of this program is to provide entertainment and psychological treatment in order to reduce the impact of their past trauma. The essence of this research is that Trauma Healing activity is very important for disaster victims It is necessary to have cooperation from various parties to help each other in handling trauma experiences, because the journey of life it will be very long and the disaster victims need to be heal from their wounds.